Effect of Curing Regime on Compressive Strength of Concrete Containing Malaysian Laterite Aggregate - Norul Wahida, Kamaruzaman; Khairunisa, Muthusamy (Trans Tech Publications, Switzerland, 2012)
Concrete subjected to improper curing process would exhibit poor strength performance due to incomplete hydration process. This research investigate the effect of curing regime towards compressive strength of concrete containing Malaysian laterite aggregate (MLA) as partial coarse aggregate replacement. Concrete specimens produced using a range of laterite aggregate replacement from 0 to 50% were placed in different curing regime namely water curing, natural weather curing and air curing until the testing date. Specimens were subjected to compressive strength test in accordance to BS EN 12390 at 60 days. The results show strength of all specimens except the air cured samples increase as the curing age become longer. It was found that water curing is the most suitable for better performance of laterite concrete. The presence of water throughout the curing process is very much crucial for laterite concrete strength developement compared to normal concrete.